“A hora e vez de Augusto Matraga: uma análise semiótica da adaptação de Antunes Filho” - Silva, Fabrício Floro e (2013)
The present study analyzes “Augusto Matraga’s Hour and Turn”, theatrical adaptation of João Guimarães Rosa’s homonymous short story, made by stage director Antunes Filho in 1986, through the theoretical framework of French Semiotics, observing how this process of translation is done, turning Rosa's literary work into a play. We will apply mainly the discursive level of the meaning generative process to the texts to observe how the enunciator Antunes recovers, in Rosa’s story, the figures and themes expressed and therefore, analyze which elements from the source text remain, are emphasized or put in the background of the adapted text. We will also examine in which ways Antunes Filho, as enunciator, establishes intertextual relations with other texts by Guimarães Rosa to create his adaptation. In the texts, the protagonist, the actor Augusto Matraga, after living as a figure of evil incarnate, changes his behavior, leading to a major change in his life, ultimately being regarded as holy. In both texts we have the manifestation of an actor who can be considered a myth because he brings traces of humanity and sainthood. Therefore, our aim is to observe how the adapted text recreates Matraga’s performance and presents identities and differences compared to the source text, especially in terms of syntax and discourse semantics of the texts. Keywords: Semiotics; Adaptation; Antunes Filho; João Guimarães Rosa.